Optimalisasi Layanan PAUD Holistik Integratif untuk Mewujudkan Pendidikan Anak Usia Dini Berkualitas - Aslindah, Andi; Sjamsir, Hasby; Ika Pratiwi, Yuni; Brantasari, Mahkamah; Ardiana, Reni; Mailina (Jurnal Pengabdian Kepada Masyarakat Patikala, 2026)
Most PAUD services in Samarinda City are not yet comprehensive; many focus solely on education and health without integrating nutrition, caregiving, and child protection aspects. Limited teacher knowledge and lack of institutional partnerships remain major challenges. This community service aimed to provide understanding and reinforcement related to implementing Holistic Integrative PAUD (PAUD HI) to enhance service quality. The activity was conducted through a hybrid seminar in January 2025 involving 148 participants (teachers, principals, foundation managers, and early childhood education practitioners). Results indicated improved participants’ understanding of the PAUD HI concept, the urgency of multisector partnerships, and practical implementation strategies. Discussions identified four key issues: limited human and financial resources, need for strategic partnerships, success indicators of PAUD HI, and parent-community involvement. In conclusion, this program strengthened educator capacity and promoted  cross-sector collaboration to realize quality early childhood education.